Researching society and culture - Seale, Clive (Los Angeles ; London : Sage, 2018)
"From starting out to generating, analysing, and presenting real-world data, this book covers social research and research methodology foundations and sits on the pulse of topics like digital social research, social surveys, and big data. It gives readers the tools to: design the right research question; access, understand, and use existing data; write up projects and assignments effectively; [and] be confident in the A to Z of the research process. Packed with international examples and supported by videos, datasets, templates, and additional exercises, this book is the perfect hand-holder for any social science student starting a methods course or project"--Back cover.
Includes bibliographical references (pages 617-636) and index.
Keywords: Social sciences -- Methodology; Social sciences -- Philosophy; Social sciences -- Research; Sociology -- Methodology; Sociology -- Philosophy; Sociology -- Research; Culture -- Research; Culture -- Research; Social sciences -- Methodology; Social sciences -- Philosophy; Social sciences -- Research; Sociology -- Methodology; Sociology -- Philosophy; Sociology -- Research; Empirische Sozialforschung; Gesellschaft; Kultur; Sozialwissenschaften; Kultursoziologe; Methodologie; Society